Euthalian Traditions : Text, Translation and Commentary. - Blomkvist, Vemund (Berlin : De Gruyter, 2012)
The auxiliary material preserved in New Testament manuscripts has been neglected by scholars. The present study treats the Euthalian paraphrases and the biblical text of Acts and the Letters together, as a 'system'. The book is of interest to students of the reception of the New Testament. It also includes a study on the meta-terminology of the apparatus, written in collaboration with David Hellholm.
Print version record.
Includes bibliographical references (pages 345-376) and indexes.
Master record variable field(s) change: 630
Keywords: Euthalian apparatus; Bible. -- Paraphrases, Greek -- History and criticism; Bible. -- Criticism, interpretation, etc. -- History; Bible. -- Criticism, Redaction; Bible. -- Criticism, Redaction; Bible. -- Criticism, Redaction; Bible. -- N.T. -- Acts -- Criticism, Redaction; Bible. -- N.T. -- Catholic Epistles -- Criticism, Redaction; Bible. -- N.T. -- Criticism, interpretation, etc. -- History; Bible. -- N.T. -- Epistles of Paul -- Criticism, Redaction; Bible. -- N.T. -- Paraphrases, Greek -- History and criticism; BIBLES -- English Standard Version -- New Testament & Portions; BIBLES -- New American Standard Bible -- New Testament & Portions; Electronic books; Electronic books